2014
DOI: 10.3390/ijms15045292
|View full text |Cite
|
Sign up to set email alerts
|

Beclin 1 Expression in Ovarian Tissues and Its Effects on Ovarian Cancer Prognosis

Abstract: Beclin 1 is an autophagy-associated protein involved in apoptosis and drug resistance, as well as various malignancies. We investigated the expression of Beclin 1 protein in ovarian epithelial tissues and correlated it with the prognosis of ovarian cancer. Beclin 1 protein expression was determined using immunohistochemistry in 148 patients with ovarian epithelial cancer, 26 with ovarian borderline tumor, 25 with benign ovarian tumor, and 30 with normal ovarian tissue. The relationships between Beclin 1 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 21 publications
7
45
1
Order By: Relevance
“…Therefore, an increased frequency of follow-up in patients with loss of BECN1, to detect recurrence earlier, may allow patients to quickly receive further beneficial cytoreductive surgery or second-line chemotherapy. Multiple previous studies have demonstrated comparable data in line with the present study, in that the loss of BECN1 was reported to be associated with an unfavorable prognosis of several solid cancers, including ovarian carcinoma (15,(25)(26)(27). In contrast, other studies demonstrated that the loss of BECN1 was significantly correlated with improved survival in patients with endometrial cancer, renal cell cancer, and colorectal cancer (28)(29)(30).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Therefore, an increased frequency of follow-up in patients with loss of BECN1, to detect recurrence earlier, may allow patients to quickly receive further beneficial cytoreductive surgery or second-line chemotherapy. Multiple previous studies have demonstrated comparable data in line with the present study, in that the loss of BECN1 was reported to be associated with an unfavorable prognosis of several solid cancers, including ovarian carcinoma (15,(25)(26)(27). In contrast, other studies demonstrated that the loss of BECN1 was significantly correlated with improved survival in patients with endometrial cancer, renal cell cancer, and colorectal cancer (28)(29)(30).…”
Section: Discussionsupporting
confidence: 72%
“…According to previous studies, the positive rates of Beclin 1 were significantly higher in ovarian cancer than in benign ovarian tumor or normal ovarian tissue (15 Hospital approved the examination of tumor tissues and the research was conducted according to the Declaration of Helsinki. Written informed consent was obtained from all of the subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Decreased Beclin 1 proteins have been reported in breast cancers compared to normal tissue [2,31], as well as in other cancer entities, such as ovarian carcinomas [32,33], colon cancer [34,35], non-small cell lung cancer [36,37], cholangiocarcinoma [38], gastric cancer [39,40], and renal cell carcinoma [41]. A poorer prognosis of patients expressing low Beclin 1 levels has also been reported in multiple tumor entities, such as breast [30,42], ovarian [32,33], oral [43], gastric [39,40], and renal cell carcinoma [41].…”
Section: Mutation Status Of Beclin 1 In Cancermentioning
confidence: 99%
“…Beclin 1 is a proven autophagy-associated protein that promotes autophagy and plays a tumorsuppressive role in the lysosomal degradation pathway of autophagy [28]. Our previous experiments confirmed that patients with higher Beclin 1 expression had a better prognosis than those with lower Beclin 1 expression [29]. LC3 is a key protein involved in autophagy and an important marker for monitoring this process.…”
Section: Discussionmentioning
confidence: 53%